Analisis Kesesuaian Aplikasi Pengadaan Menggunakan Metode Task Technology Fit (Ttf) pada PT ABC - nazhmii lafiona; Ma’mun Sutisna (Ebiz Prima Nusa, 2023)
Digitalization has entered the world of the office with the aim of helping the tasks of each employee. PT ABC in the procurement division has implemented electronic procurement, namely the procurement process using digital by presenting the procurement application. The purpose of the study was to determine the suitability of the procurement application for procurement performance. Implementing digital requires compatibility with the tasks owned by everyone, this suitability can be analyzed using the Task Technology Fit method. The research method used is descriptive of quantitative approaches and collection techniques by distributing questionnaires to 111 active users of the procurement application at PT ABC. The results showed that there was data quality in accordance with user needs in a very good category, there was data locability in accordance with user needs in a very good category, there was also user authority in accessing procurement application in accordance with user needs, there was compatibility in accordance with user needs in a very good category and finally the results showed that there was a relationship with users in a very good category. As a result, the procurement application was in accordance with the Task Technology Fit method. Keywords: Application fit, Procurement, Task Technology Fit